A case of overshunting‐associated myelopathy that developed 27 years after placement of a ventriculoperitoneal shunt. Issue 3 (8th March 2021) - Fujimori, Juichi; Kikuchi, Hirokazu; Kameyama, Masayuki; Haryu, Shinya; Sato, Kenichi; Sasaki, Tatsuya; Ozawa, Hiroshi; Murata, Takaki; Nakashima, Ichiro
Abstract: Overshunting‐associated myelopathy (OSAM) is a rare complication of ventriculoperitoneal (VP) shunts. Here, we report the case of a 52‐year‐old man who presented with OSAM without positional headache 27 years after the placement of a VP shunt. The patient recovered after shunt ligation and transection. Although rare, chronic cerebrospinal fluid overdrainage can lead to cervical myelopathy due to spinal cord compression by the dilated vertebral veins/epidural venous plexus. Thus, reversible OSAM needs to be differentiated during the diagnosis of cervical myelopathy.